Sejarah Peristilahan Tarbiyah Dan Taklim Dalam Tinjauan Filsafat Pendidikan Islam - Imroatun Imroatun; Ilzamudin Ilzamudin (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2020)
The terms in the philosophy of Islamic education need more attention because of the variety of content and methods that sometimes appear paradoxes in their studies. This could be the result of the theoritization of Islamic education which was still dominated by classical Islamic thinkers in the pre-modern era. Moreover, the term philosophy is still not recognized as a part of comprehensive Islamic studies. Through historical research, this article intends to explore further the basic terms of Islamic education which are infused from Arabic. Rather than other terms, ta'dib has a historical syncornization and scope that corresponds to the fact that education is a human right in a scope that includes the basics in the Quran and Hadith.